Reaction kinetics analysis of branched-chain alkyl esters of palmitic acid and cold flow properties. (March 2020) - Ni, Zihao; Zhai, Yuling; Li, Fashe; Wang, Hua; Yang, Kai; Wang, Bican; Chen, Yu
Abstract: Preparation of methyl palmitate, isopropyl palmitate, isobutyl palmitate, and isoamyl palmitate was carried out using pyridine n -butyl bisulfate ionic liquid as catalyst in a self-designed reactor to catalyze esterification reaction of palmitic acid with methanol, isopropanol, isobutanol, and isoamyl alcohol, respectively. According to the single-factor experimental results, an orthogonal test of four factors and three levels was carried out for branched-chain alkyl esters of palmitic acid under different reaction time, reaction temperature, and catalyst dosage. Verification test was conducted under the optimal conditions, and the conversion in all the cases was up to 97%. Analysis of the reaction kinetics of methyl palmitate, isopropyl palmitate, isobutyl palmitate, and isoamyl palmitate was carried out by the integral method. Reaction order, frequency factor, activation energy, and reaction kinetic model were determined. Compared to methyl palmitate, the kinematic viscosity of the branched-chain alkyl esters of palmitic acid was slightly higher; however, the solidifying point (SP) and cold filter plugging point (CFPP) decreased with increasing degree of branched-chain. The CFPP reduced by up to 15 °C. Therefore, the use of branched-chain alcohol instead of methanol ester exchange descaling method can effectively reduce the SP and CFPP of biodiesel to improve its cold flow properties. Highlights: Conditions for branched-chain alkyl esters of palmitic acid were optimized. The reaction kinetic parameters and reaction kinetic model were determined. It can be used as component of biodiesel alone with good cold flow properties.